REDESAIN BODY MOBIL MATARAM PROTO V5 DENGAN MEMPERTIMBANGKAN ASPEK AERODINAMIS - Aji Pranoto; Septa W; Yudha Orienta; Wisnu Y Santika (Jurnal Pendidikan Vokasi Otomotif, 2021)
The Energy Saving Car Contest (KMHE) is a contest organized by the Ministry of Research, Technology and Higher Education (Kemenristekdikti). This is a contest among students to make a national level fuel efficient vehicle. The purpose of designing this design is to produce an energy-efficient car body design "Mataram Proto" and to produce a vehicle that has a good aerodynamic level. This design of the car body is designed elegantly but still has good aerodynamics and does not reduce the safety aspects of the driver. The process of making a car body design uses Autodesk Inventor and the process of aerodynamic analysis of the Mataram Proto car body uses Ansys Mechanical software. Aerodynamic testing was carried out at an air speed of 45 km / h or 12.5 m / s. From the previous Mataram Proto body test results, the drag coefficient was 0.233 and the lift coefficient was 0.1887 and from the Mataram Proto V5 car body test, the drag coefficient was 0.47 and the lift coefficient was 9.95. From the results of this test, it shows that the previous Mataram Proto car body had a better aerodynamic level due to the difference in the input of different airspeed variables, where the air velocity on the previous Mataram Proto car body was 40 (km / h) and the air speed on the Mataram Proto V5 body. amounting to 45 (km / hour).